Pengaruh Penggunaan Mulsa Terhadap Kelembaban Tanah Dan Konservasi Air - Arni Lestari Waruwu; Natalia Kristiani Lase (Jurnal Ilmu Pertanian dan Perikanan, 2026)
The use of mulch is one of the effective soil and water conservation techniques to increase soil moisture and water use efficiency on agricultural land. Mulch functions to suppress the rate of water evaporation from the soil surface, maintain temperature stability, improve soil structure, and support microorganism activity. This literature review aims to understand the effect of mulch use on soil moisture and water conservation based on previous research results. The results of the review show that the provision of mulch, both organic and inorganic, can significantly increase soil moisture by reducing evaporation, increasing water infiltration, and maintaining soil temperature stability. However, excessive mulch thickness can interfere with soil aeration and root respiration processes, so it needs to be adjusted to land conditions and plant types. Therefore, the proper use of mulch can be an important strategy in sustainable soil and water management, especially on agricultural land in tropical and dry areas.